2018
DOI: 10.1111/jocn.14532
|View full text |Cite
|
Sign up to set email alerts
|

The association of sociodemographic factors and needs of haemodialysis patients according to Maslow's hierarchy of needs

Abstract: Healthcare providers should not only focus on the patients' physiological needs, but should determine and address their other needs in various aspects in order to improve the quality and efficacy of the dialysis care process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
11
0
4
Order By: Relevance
“…One prominent theory concerning needs is Maslow's hierarchy, which clarifies the needs considered fundamental to all humans: physiological, safety, belongingness and love, esteem, and self‐actualization . These needs cover all aspects—physical, psychological, and social—of human life, and the theory has achieved popularity in diverse contexts . Given that breast cancer and its treatment influence needs related to all aspects of patients' lives, this theory is helpful across the treatment and rehabilitation process.…”
Section: Introductionmentioning
confidence: 99%
“…One prominent theory concerning needs is Maslow's hierarchy, which clarifies the needs considered fundamental to all humans: physiological, safety, belongingness and love, esteem, and self‐actualization . These needs cover all aspects—physical, psychological, and social—of human life, and the theory has achieved popularity in diverse contexts . Given that breast cancer and its treatment influence needs related to all aspects of patients' lives, this theory is helpful across the treatment and rehabilitation process.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that QoL depends on the age to have better scores, and the maximal age to achieve them is 30 years (Salim et al, 2019;Silva and Mattos, 2019;van Sandwijk et al, 2019). In relation to the pain domain, in the current research, younger patients present less pain, and can be explained by a study that identifies that, after transplantation, there is a significant organic improvement, in addition to the fact that this treatment decreases the number of invasive procedures and avoids the development of pain due to the various complications related to long hemodialysis treatments (Melo et al , 2019;Shih et al, 2019). As for vitality, the research brought an improvement in QoL due to age.…”
Section: Discussionmentioning
confidence: 69%
“…O tratamento da IRC compreende o convencional (terapêutica medicamentosa e dietética) e a terapia renal substitutiva que se torna necessária no último estágio de evolução, podendo ser a hemodiálise, a diálise peritoneal ou o transplante renal (2) . A hemodiálise exige que o paciente dependa de uma máquina e realize mudanças em sua rotina e hábitos de vida, o que limita a liberdade, causa estresse mental e econômico, redução da interação social, entre outras mudanças (3) .…”
Section: Introductionunclassified